Immunohistochemical Expression of Nestin as Cancer Stem Cell marker in Gliomas - Rasha Mokhtar Abdelkareem; Afaf T Elnashar; Khaled Nasser Fadle; Eman MS Muhammad (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2019)
Background: Gliomas represent the most frequent primary tumors of central nervous system (CNS), contributing to more than half of the incidence of brain tumors. Cancer stem cell markers (CSC) identify a group of patients at high risk for progression. Nestin is an intermediate fi lament (IF) protein was fi rst described as a neural stem cell/progenitor cell marker. Nestin-positive neuroepithelial stem cells are detected in the subventricular zone of the human adult brain and they remain mitotically active throughout adulthood. The expression of Nestin in gliomas has been suggested to be related to dedifferentiation, improved cell motility, invasive potential and increased malignancy. This study aims to investigate Nestin immunohistochemical expression in different types of glioma and its correlation with different clinicopathological parameters.